RELIABILITAS INSTRUMEN GCS DAN FOUR SCORE UNTUK MENILAI TINGKAT KESADARAN PASIEN DI RUANG ICU - Ika Silvitasari, Hery Djagat Purnomo, Untung Sujianto (STIKes Adi Husada, 2017)
Instrumen untuk menilai tingkat kesadaran secara umum menggunakan GCS, ada instrumen lain yaitu FOUR score sebagai alternatif penilaian tingkat kesadaran. Kelemahan dari instrument GCS yaitu tidak dapat menilai respon verbal pada pasien yang terpasang intubasi dan tidak mampu menilai pasien dengan keadaan vegetatif. Jenis penelitian ini adalah studi observasional. Sampel yang digunakan sebanyak 74 responden di ruang ICU. Responden diobservasi tingkat kesadaranya oleh dua orang observer untuk mengetahui nilai reliabilitas. Hasil uji reliabilitas dengan menggunakan uji Kappa didapatkan hasil nilai Kappa GCS (E:0,816; M:0,861;V:0,904) sedangkan FOUR score (E:0,863;M:0,785;B:0,623;R:1). Nilai total Kappa dari instrumen GCS adalah 0,973 dan FOUR score 0,888. Kedua observer memiliki nilai rata-rata nilai Kappa dari rentang baik – sangat baik. Penelitian lebih lanjut perlu dilakukan untuk mengetahui sensitivitas dan spesifisitas GCS dan FOUR score. ABSTRACT Instruments to assess the level of consciousness in general use GCS, there is a new instrument that is FOUR score as an alternative assessment of the level consciousness. The weakness of the instrument GCS is unable to assess verbal response in patients intubated and unable to assess patients with vegetative state. This type of study is an observational study. The sample used by 74 respondents in the ICU. Respondents observed level by 2 observers to determine the reliability value. Results:The reliability of the test results showed the value of Kappa GCS (E: 0,816; M: 0.861; V: 0.904) while the FOUR score (E: 0.863; M: 0.785; B: 0.623; R: 1). The total value of the instrument GCS Kappa was 0.973 and FOUR score 0.888.Conclusion: Both observer has an average value of the range of values Kappa good - very good. Recommendation: Further research should be conducted to determine the sensitivity and specificity of GCS and FOUR score. Keywords : Reliability, GCS, FOUR score. DAFTAR PUSTAKA Bordini AL, Luiz TF, Fernandes M, Arruda WO, Teive HAG. (2010). Coma scales A historical review. Arq Neurosiquiart :68(May):930–7. Bruno M-A, Ledoux D, Lambermont B, Damas F, Schnakers C, Vanhaudenhuyse A, et al. (2011). Comparison of the Full Outline of UnResponsiveness and Glasgow Liege Scale/Glasgow Coma Scale in an intensive care unit population. Neurocrit Care.;15(3):447–53. Dharma KK. (2011). Metodologi Penelitian Keperawatan. Jakarta: CV Trans Info Media. Irawan H, Setiawan F, Dewanto G. (2009). Perbandingan Glasgow Coma Scale dan Revised Trauma Score dalam Memprediksi Disabilitas Pasien Trauma Kepala di Rumah Sakit Atma Jaya.;437–42. Jalali R, Rezaei M. (2014). A Comparison of the Glasgow Coma Scale Score with Full Outline of Unresponsiveness Scale to Predict Patients ’ Traumatic Brain Injury Outcomes in Intensive Care Units. Critical care research and practice.Critical Care Research. Volume 2014. Kavipat PA. (2009). Endorsement of the FOUR Score for Consciousness Assessment in Neurosurgical Patients. Acta Med Okayama;4. Matheesiriwat N, Kuptniratsaikul S. (2012). The FOUR Score and Glasgow Coma Scale to Evaluate the Patients with Intubation at Emergency Room. Royal Thai Army Medical Journal;145–52. Peng J, Deng Y, Chen F, Zhang X, Wang X, Zhou Y, et al. (2015). Validation of the Chinese version of the FOUR score in the assessment of neurosurgical patients with different level of consciousness. BMC Neurol.;15(1):254. Sahin et.al. (2015). Comparision Of GCS And FOUR Scores Used In The Evaluation OfNeurological Status In Intensive Care Units. Journal of Contemporary Medicine 2015;5(3): 167-172. DOI: 10.16899/ctd.99371. Smeltzer, Suzanne C, Bare, Brenda G. (2010). Brunner & Suddarth’s textbook of medical-surgical nursing. Edisi 12. Wolters Kluwer Health / Lippincott Williams & Wilkins.Stead LG, Wijdicks EFM, Bhagra A, Kashyap R, Bellolio MF, Nash DL, et al. (2009). Validation of a new coma scale, the FOUR score, in the emergency department. Neurocrit Care;10(1):50–4. Tadrisi SD, Bahari N, Ebadi A, Madani SJ. (2012). Validity and reliability of coma scale (four score) in adult patient hospitalized in Critical Care Units.;5(2):95–102. Wijdicks EFM, Bamlet WR, Maramattom B V, Manno EM, McClelland RL. (2005). Validation of a new coma scale: The FOUR score. Ann Neurol.Oct;58(4):585–93. DOWNLOAD FULL TEXT >>